Magnetic and Electric Properties of Sr2-xYxCoO4, (0.50≤x≤0.80) Layered Perovskites. (7th May 2013) - Ali, A. I.; Hassen, A.
Abstract : The electric and magnetic properties of Sr 2 - x Y x CoO 4 layered perovskites have been investigated systematically over the doping range 0.50 ≤ x ≤ 0.80 . It was found that both Sr1.5 Y0.5 CoO4 and Sr1.4 Y0.6 CoO4 undergo ferromagnetic (FM) transition around 145 K and 120 K, respectively. On the other hand, Sr1.3 Y0.7 CoO4 and Sr1.2 Y0.8 CoO4 compounds showed paramagnetic behavior over a wide range of temperatures. In addition, spin-glass transition (T SG ) was observed at 10 K for Sr1.3 Y0.7 CoO4 . All investigated samples are semiconducting-like within the temperature range of 10–300 K. The temperature dependence of the electrical resistivity, ρ ( T ), was described by two-dimensional variable range hopping (2D-VRH) model at 50 K < T ≤ 300 K. Comparison with other layered perovskites was discussed in this work.